Morphometric investigations in mitral stenosis using two dimensional echocardiography. Issue 1 (July 1982) - Schweizer, P; Bardos, P; Krebs, W; Erbel, R; Minale, C; Imm, S; Messmer, B J; Effert, S
Abstract : A method is proposed for comparing the orifice size and the morphology of stenotic mitral valves, removed intact at the time of replacement, with the preoperative two dimensional echocardiographic cross-sections. The excised mitral valve apparatus is suspended on a specially constructed mounting. To avoid shrinkage the orifice is stabilised with an airfilled balloon. A radiography is taken directing the x-ray beam perpendicular to the valve orifice. In 40 of 51 patients this method provided the means of relating the echocardiographic cross-sections to the morphology of the valve. Planimetry of the valve area compared favourably with the postoperatively determined orifice size. Agreement was found in 34 of 40 patients in orifice shape between preoperative echocardiograms and x-rays of th excised valve. The relation between intraoperative estimation of size of the valve, using dilators with known diameters, and the postoperative results was less favourable. Areas of calcification were identified on echocardiography as dense conglomerate echoes. In 30 patients (75%) the localisation of calcium deposits and in 67% the degree of calcification was in agreement with the x-rays of the valve taken after operation. In addition to determination of the area, two dimensional echocardiography allows detailed studies of the stenotic valves, and is of particular importance for planning operative treatment.